Can the G7 be a force for good in the current global food security crisis? - Laborde Debucquet, David; Smaller, Carin (International Food Policy Research Institute, 2023)
The Group of Seven wealthy nations (G7), currently led by the German presidency, has put a welcome focus on the global food insecurity and nutrition crisis unleashed by the war in Ukraine, with the most severe impacts falling on vulnerable populations in low- and middle-income countries (LMICs). Two G7 meetings in May pro duced four separate communiqués, each of them dozens of pages long (the development ministers’ commu niqué alone was 23 pages!), and a G7-led Global Alliance for Food Security was announced. The G7 meetings coincided with serious efforts on the same front by the United Nations, which has set up a Global Crisis Response Group and convened a UN Security Council meeting on Food Insecurity and Conflict. The G7 effort can help to ensure a commensurate response to what is turning out to be the worst glob al hunger crisis in decades, and in so doing help to elevate the G7 itself, whose relevance as an exclusive group of rich and elite countries has been questioned. To realize this promise, however, G7 commitments must be backed up with action — particularly funding.